Implications of Advertising, Social Media, Product Quality, and Satisfaction on Intention to Purchase Skintific Skincare Products in Panai Hulu District - Winda, Fitri Dwi Sri; Harahap, Nova Jayanti; Indra, Aulia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze Advertising Implications, Social Media, Quality Products, and Satisfaction to Purchase Scientific Skincare Products in the Panai Hulu District. The research method used in this research is quantitative. In this study, the population is an unknown number of Skintific Skincare consumers in the Panai Hulu District. Research samples using incidental sampling techniques are techniques for determining samples based on chance, that is, anyone who happens to meet the researcher can be used as a sample if it is deemed that the person they meet by chance is suitable as a data source. This research uses a non-probability sampling technique because the number of members of the population is unknown, and purposive sampling is the sample determination technique. Because the exact size of the member population is not known, the sample size was calculated using the Cochran formula with a research sample of 96 people. The data collection techniques used were observation, documentation studies, and questionnaires. The analytical method for this research is multiple linear regression with the SPSS program. The research results prove that advertising has a positive and significant effect on product purchase intentions at Skintific Skincare in Panai Hulu District. Social media has a positive and significant effect on product purchase intentions at Skintific Skincare in Panai Hulu District. Product quality has a positive and significant effect on product purchase intentions at Skintific Skincare in Panai Hulu District. Satisfaction has a positive and significant effect on the intention to purchase products at Skintific Skincare in Panai Hulu District. Advertising, Social Media, Product Quality, and Satisfaction simultaneously have a positive and significant effect on the Intention to Purchase Products at Skintific Skincare in Panai Hulu District. The coefficient of determination is 0.639, meaning that Product Purchase Intention can be explained by the variables Advertising (X1), Social Media (X2), Product Quality (X3), and Satisfaction (X4) of 63.9%, while the remaining 36.1% can be explained by the variable others not examined in this study.